Pedagogia em ambiente não escolar: a atuação do pedagogo no Hospital Municipal de Castanhal. - PANTOJA, Edileuda Costa (2018)
Hospitalization in a person's life can be detrimental to the emotional condition of the being, especially when it is a child, because the hospital is an environment considered by many to be hostile and unknown. The objective of this study was to demonstrate how the educational professional is inserted in the job market outside the school environment, in this case, our research site was the hospital. As specific objectives we seek to discuss in the light of the theoretical reference the Pedagogy in Non-Formal Environment; understand the pedagogy in the hospital, some ways of acting of the pedagogue and finally, identify the relevance of the Hospital Pedagogy in the rehabilitation of the hospitalized child / adolescent in the conception of the pedagogue. For, hospital pedagogy is a modality that broadens the market of the pedagogue's performance. Based on this, this research was developed at the Municipal Hospital of Castanhal (HMC), which attends to the Unified Health System (SUS) offering some kind of pedagogical activity to hospitalized children / adolescents. In order to perform the research, we used: field research, bibliography and observation in the research environment. The results pointed to a pedagogical practice that contributes to the improvement of the hospitalized and a good acceptance of the management team of the HMC.